2014
DOI: 10.3233/jvr-130660
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between participation in Project SEARCH and job readiness and employment for young adults with disabilities

Abstract: BACKGROUND: Although there are currently more than 200 Project SEARCH programs throughout the U.S., evidence supporting the program's efficacy remains limited. OBJECTIVE: This pilot study examines the relationship between participation in Project SEARCH, a business-led transition program, and job readiness and employment rates of 10 young adults with disabilities. METHODS: Baseline and end-of-year data were gathered on participants' job readiness skills using a 29-item Job Readiness Assessment Tool (JRAT) deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…Outcome measures. Overall, measures utilised in the employment outcomes studies were primarily characterised as descriptive and observational, with several studies developing their own outcome tools (Howlin and Moss, 2012;Lorenz et al, 2016;Müller and Vangilder, 2014;Ohl et al, 2017). Outcomes were reported according to job type, hours worked, wages earned, and support services required and were supplemented by employee self-reports and anecdotal employer accounts of job performance.…”
Section: General Articles Relating To Employment Outcomes (K = 98)mentioning
confidence: 99%
“…Outcome measures. Overall, measures utilised in the employment outcomes studies were primarily characterised as descriptive and observational, with several studies developing their own outcome tools (Howlin and Moss, 2012;Lorenz et al, 2016;Müller and Vangilder, 2014;Ohl et al, 2017). Outcomes were reported according to job type, hours worked, wages earned, and support services required and were supplemented by employee self-reports and anecdotal employer accounts of job performance.…”
Section: General Articles Relating To Employment Outcomes (K = 98)mentioning
confidence: 99%
“…Wehman and colleagues (2016), in a randomized controlled trial of Project SEARCH plus Autism Spectrum Disorder Supports (PS-ASD), showed that students with significant needs who participate in internships with job and behavioral supports are more likely to gain employment than students who do not receive these services. Other research has demonstrated an increased chance of postsecondary employment and job readiness through participation in SEARCH training (Muller & VanGilder, 2014).…”
Section: Internships and Work-based Learningmentioning
confidence: 99%
“…Direct, hands on work experiences prior to exiting high school enable students with disabilities to learn not only job skills but also to acquire the "soft skills" that greatly facilitate CIE (Muller & VanGilder, 2014;Wehman et al, 2016). Soft skills, or workplace social skills, such as greeting coworkers, engaging in appropriate break room conversation, and making eye contact are important to workplace success (Morningstar, Lombardi, Fowler, & Test, 2017).…”
Section: Internships and Work-based Learningmentioning
confidence: 99%
“…According to the National Technical Assistance Center on Transitions (NTACT), such instruction is an essential characteristic of early work experiences as a predictor to improve independent living outcomes (NTACT, 2018). Müller and VanGilder (2013) found that interns who were offered jobs at the end of one year in a Project Search program that included skills instruction scored higher on a job readiness assessment than their peers who were not offered jobs. In a national Delphi study, 35 national experts in Vocational Rehabilitation (VR) reached a consensus on a list of the top 26 promising or evidence-based VR practices.…”
Section: Introductionmentioning
confidence: 94%